Flexible cystoscopy and laser stone fragmentation via Mitrofanoff stoma: A case series. (September 2022) - Conway, Joanne M; Christodoulidou, Michelle; Reid, Sheilagh; Patterson, Jake M
Objective: This case series aimed to demonstrate that flexible cystoscopy and laser stone fragmentation via a Mitrofanoff stoma is possible and an effective treatment for symptomatic bladder stones in complex patients with inaccessible urethras and challenging anatomy. Patients and methods: We present three cases which were managed in a tertiary centre. The procedure involved using a flexible cystoscope via the Mitrofanoff stoma and laser stone fragmentation without the need for an access sheath. Results: This technique was performed safely and demonstrated successful bladder stone clearance on follow-up, with no postoperative complications. Conclusion: Our case series illustrates a technique that can be performed in this select group of patients in specialist centres with the relevant surgical exposure and expertise. Level of evidence: Level 4.